Parent and child emotion and distress responses associated with parental accommodation of child anxiety symptoms. Issue 7 (15th February 2020) - O'Connor, Erin E.; Holly, Lindsay E.; Chevalier, Lydia L.; Pincus, Donna B.; Langer, David A.
Abstract: Objective: Parental accommodation contributes to the maintenance of child anxiety and related symptoms. The current study examines the contributions of parent and child factors to parental accommodation in a sample of anxious youth. Methods: Sixty‐four treatment‐seeking youth (6–16 years) and their mothers, as well as a subset of fathers ( N  = 41) reported on parental accommodation, parental distress and emotion regulation, child psychopathology, child externalizing behaviors, and child intolerance of uncertainty. Results: Parental accommodation was not related to parental distress or emotion regulation. Parents who viewed their child as being more symptomatic (e.g., anxious, externalizing, and intolerant of uncertainty) were more likely to engage in accommodation. For mothers, child anxiety and externalizing symptoms were notable predictors of accommodation. Conclusions: Parent perceptions of child symptomology is an important factor significantly related to accommodation behaviors. This finding can be used to inform programming designed to target parental responses to child anxiety and related disorders.